Comprehensible science : ICCS 2021 - International Conference on Comprehensible Science (2021); Antipova, Tatiana (Cham, Switzerland : Springer, 2022)
This book gathers selected papers that were submitted to the 2021 International Conference on Comprehensible Science (ICCS 2021) that aims to make available the discussion and the publication of papers on all aspects of single and multi-disciplinary research on conference topics. ICCS 2021 held on June 1819, 2021. An important characteristic feature of conference is the short publication time and worldwide distribution. Written by respected researchers, the book covers a range of innovative topics related to: artificial intelligence research; big data and data mining; blockchain and cryptocurrency; business, finance and accounting and statistics; cyber security systems; ecology systems; educational technologies; engineering and technology; innovative economics; media technologies; medicine, public health and rehabilitation; nutrition and diet researches; physical and material sciences; and smart cities and contracts. This book may be used for private and professional non-commercial research and classroom use (e.g., sharing the contribution by mail or in hard copy form with research colleagues for their professional non-commercial research and classroom use); for use in presentations or handouts for any level students, researchers, etc.; and for the further development of authors scientific career (e.g., by citing and attaching contributions to job or grant application).
Part I. Artificial Intelligence Research -- Methods of Neural Network Modeling of Clusterization of Taxpayers to Determine Credit Risk by a Financial Regulator -- Machine Learning Approach on Burnout -- The Case of Principals from Southern Israel -- Part II. Big Data and Data Mining -- A Data Mining Analysis of Cross-Regional Study of Apparel Consumption -- Part III. Blockchain and Cryptocurrency -- Portfolio Optimization with Investment in Cryptocurrencies -- Modeling the Dynamics of the Value of Digital Financial Assets Using the Example of Bitcoin, Ethereum and Ripple -- Business, Finance and Accounting and Statistics Insights from Some Governments’ Budget Functional Expenditures for the Fifteen Years: 2005–2019 -- Why Do German Car Manufacturers Get Engaged in Mobility Concepts? -- Classification of Factors Affecting the Development of Rural Areas -- Russian Economic Policy in the Late 17 th–Early 18 th Centuries: The Case of the Tobacco Monopoly -- Digital Technologies for Prudent Public Debt Management -- Assessing the Convergence of the Digital Infrastructure Development in the RF Regions: Spatial Analysis -- Development of Methodological Approaches to Disclosure of Equity Information in Non-financial Statements of a Commercial Organization -- Modeling of Forecasting Financial Statement -- Creative Accounting: Current Trends in Foreign Studies -- Part IV. Cyber security systems -- Detecting the Attacks to DNS -- Investigating Cyber Security Awareness (CSA) Amongst Managers in Small and Medium Enterprises (SMEs) -- Part V. Ecology systems -- Green Economy: Current Trends and Financial Aspects of Development -- Shaping an Effective Ecosystem of the Regional Digital Economy in the Context of Uneven Digital Development -- Part VI. Educational technologies -- The Relationship Between Life Satisfaction, Engagement, and Burnout - Application to Higher Education Teachers in Portugal -- Scrum Embedded in the Blogs Approach for Education -- A Conceptual Framework for Teaching Strategy Analysis -- Part VII. Engineering and technology -- Using the Basin Modeling Apparatus in Geological Exploration for Oil and Gas -- Assessment of Geological Risks When Performing Prospecting and Exploration for Oil and Gas -- Part VIII. Innovative economics -- Model of the System of Innovative and Consulting Services for Agricultural Entities -- A Syndinic Approach to Enterprise Risk Management -- Are Consumers Really Informed on Corporate Social Responsibility Labels for Fishery Products? Results of an Italian Case Study -- National Financial System Challenges During Modern Economy Growth -- Part IX. Features of Consolidation of the Ukrainian Nation in the Conditions of Decentralization -- Journalistic, Advertising and Political Message in the Digital Age -- Authorship Attribution of Russian Social Media Texts: Does the Volume of Data Favor Idiolect Identification? -- Building the Identity of a Corporate Brand. Case Study: Banca Transilvania (Transilvania Bank) -- Global Research Trend on Social Media for Election: A Bibliometrics Analysis -- Part X. Medicine, Public Health and Rehabilitation -- Trajectory Correction for Visually Impaired Athletes on 100 m Paralympic Races -- Autonomic Dysregulation Syndrome in Covid-19 Convalescents: Possible Causes and Approaches to Its Correction -- Use of Mobile Applications in Alternative Treatment for Post- traumatic Stress Disorder in Women Victims of Aggression -- Interleukin IL-1b Receptor Complex -- A Strategic Model of a Medical Organization in the Context of Cognitive Transformation of the World -- Part XI. Nutrition and diet researches -- Study of the Quality of Goat’s Milk and Innovative Ways of Its Processing -- Part XII. Physical and material sciences -- Transients in Acoustic Emission of the Organic Self-propagating High-Temperature Synthesis -- Effect of Modification on Strength Properties Functional Composites -- Optimization of the Process of Gamma Irradiation of Polyethylene Based on the Monte Carlo Method -- Part XIII. Smart cities and contracts -- Heuristic Evaluation of the Usability of Smart Home Applications.
2 Methodological Framework and Structure.
Includes author index.
Online resource; title from PDF title page (SpringerLink, viewed September 10, 2021).
Keywords: Technological innovations -- Congresses; Business -- Data processing -- Congresses; Educational technology -- Congresses; Gestion -- Informatique; Business -- Data processing; Educational technology; Technological innovations; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings